(untitled) (Journal of Educational Sciences, 2019)
This article considers the theoretical basis for training of social educators and workers. This article is for review only. The main program for studying the problem of teaching specifics on social pedagogues and workers in the Republic of Kazakhstan and Great Britain was examined from the theoretical point of view. The author identifies 4 vectors of study on this topic: 1) analysis of research, based on the theory and principles of comparative pedagogy; 2) comparative studies of the education system of Kazakhstan and foreign countries; 3) specialized studies of the training for professional social teachers and social workers in higher education institutions; 4) researches that study the education system abroad and introduce the best practices in the education system of the country. The objective background for the study is political, economic, socio-cultural problems affecting the spiritual values of society.To study the experience of the study, it is intended to analyze the comparison of studies and its results for a scientific and theoretical justification in addition to undesirable aspects. Here the ways of education system studying abroad and the introduction of best practices in the country’s education system are examined. In conclusion, there kept under review the methodology and theoretical bases of study, method of comparison, as well as research of domestic scientists on this issue and general theoretical bases of the socio-pedagogical process, moreover analyzing the training of social workers and teachers, social pedagogy, social work, activities, concepts and definitions in social pedagogical profession in the UK and Kazakhstan. Key words: social educators, social work, social pedagogy, social worker, methodology, education, individualistic pedagogy.